2008
DOI: 10.1093/eurheartj/ehn357
|View full text |Cite
|
Sign up to set email alerts
|

Impact of complete revascularization with percutaneous coronary intervention on survival in patients with at least one chronic total occlusion

Abstract: Successful CTO-PCI confers a long-term survival benefit. Improvement in survival is driven by the differences in the outcome of patients with multivessel disease and who were completely revascularized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
144
5
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(161 citation statements)
references
References 17 publications
7
144
5
5
Order By: Relevance
“…Some older registries have reported that patients with complete revascularisation have a better prognosis than those with incomplete revascularisation, including the presence of an untreated CTO (Hannan et al, 2006, Valenti et al, 2008. The SCAAR (Swedish Coronary Angiography and Angioplasty) Registry includes data from 2006 and 2010 on 23 342 patients with multivessel disease.…”
Section: Discussionmentioning
confidence: 99%
“…Some older registries have reported that patients with complete revascularisation have a better prognosis than those with incomplete revascularisation, including the presence of an untreated CTO (Hannan et al, 2006, Valenti et al, 2008. The SCAAR (Swedish Coronary Angiography and Angioplasty) Registry includes data from 2006 and 2010 on 23 342 patients with multivessel disease.…”
Section: Discussionmentioning
confidence: 99%
“…In 3 (11,13,16) of the 5 studies, C-RV was associated with reduced R-RV. In 8 (6,9-11,13-16) of the 11 studies, C-RV was associated with reduced MAC(C)E. There were a number of important issues, however, in the aforementioned studies (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) of C-RV versus IC-RV in DES-PCI for MV-CAD (except for AMI) (Figure 1). First, "angiographic" (successful angioplasty of all diseased lesions in the major epicardial coronary vessels and their first degree side branches) and "proximal" C-RV definitions (successful angioplasty of all diseased proximal arteries) according to a study by Kim et al (18) are more accurate and clinically relevant.…”
mentioning
confidence: 99%
“…Our systematic search using keywords including "complete" or "completeness"; "incomplete" or "culprit"; "revascularization"; and "drug-eluting" identified 14 studies (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) summarized in Tables 1,2. The design of all studies was a non-randomized observational study, and all but one (13) studies reported adjusted HRs for outcomes of interest in "C-RV vs. IC-RV" or "IC-RV vs. C-RV".…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Последующие значимые регистры (ERCTO, IRCTO), касающиеся проблемы эндоваскулярного лечения ХОКА, также подтвердили важность данного ангиографического показателя (протяженность окклюзии) как фактора риска в успехе ЧКВ [22]. По данным European Registry of Chronic Total Occlusion (ERCTO), длина поражения КА более 20 мм ассоциировалась с достоверно низким успехом река-нализации хронической окклюзии (отношение рисков (ОР) 9,6; 95% доверительный интервал (ДИ) 0,35-0,79, p<0,001) [23].…”
unclassified